2015
DOI: 10.4236/jbise.2015.84026
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles Induced Oxidative Damage in Peripheral Blood Cells of Rat

Abstract: Nanotechnology is a rapidly growing field that has elicited much concern due to a variety of applications in different fields such as industry, medicine, and cosmetics. These developments increase the concern among the general population. Hence, there is an urgent need to explore the possible human health effects of these nanomaterials. The present study is aimed to evaluate the cytotoxic and genotoxic effects of iron oxide nanoparticles (IONPs) in-vivo. In order to study the toxic effects, Wistar rats were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 39 publications
6
31
1
Order By: Relevance
“…Post‐fixation of sample was done in 1% osmium tetroxide and then dehydrated through an ethanol graded series and embedded in epoxy resin. Uranyl acetate and lead citrate were used for staining the ultrathin sections, later examined under Jeol Electron Microscope (JEM 2100F) at 120 kV (Gaharwar & Paulraj, ).…”
Section: Methodsmentioning
confidence: 99%
“…Post‐fixation of sample was done in 1% osmium tetroxide and then dehydrated through an ethanol graded series and embedded in epoxy resin. Uranyl acetate and lead citrate were used for staining the ultrathin sections, later examined under Jeol Electron Microscope (JEM 2100F) at 120 kV (Gaharwar & Paulraj, ).…”
Section: Methodsmentioning
confidence: 99%
“…Hematological parameters are affected by stress, environmental factors and nutritional deficiencies and hence can be used as good health indicator and are used on regular basis for the diagnosis of various diseases [24]. Gaharwar and Paulraj [25] had reported a significant decrease in red blood cells in rat that were exposed to either 15 or 30 mg/kg iron oxide. They had suggested that these changes in red blood cells are due to abnormalities induced by iron oxide in hemopoietic system that is responsible for erythrocyte production.…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide dismutase generates H 2 O 2 from super oxide free radicals that are more toxic than oxygen-derived free radicals and are detoxify by catalase and reduced glutathione [28]. Gahrawar and Pulraj [25] had reported a reduction in SOD and increased lipid peroxidation in iron oxide nanoparticle-treated rats as compared to control. In contrast, our results revealed increased SOD activity (P ¼ 0.005) and reduced lipid peroxidation (P ¼ 0.8) in liver and brain of strontium hexaferrite cobalt iron oxide-treated male mice as compared to salinetreated control group (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Among the inorganic magnetic nanomaterials used more frequently to interact with human organism, metal oxides, especially iron oxides (magnetite, maghemite), silica, titanium oxides, or zinc oxide are found [32]. These oxides, even when they are covered and present no cytotoxicity and before they could harm the living bodies as toxic elements by reaching a certain level of concentration, they could mechanically harm the organs and tissue of the body due to their inappropriate size or due to sharp feature of geometric shape.…”
Section: Introductionmentioning
confidence: 99%